The influence of respiratory infections on Henoch-Schönlein purpura in children - Bili Wang; Wenqing Xiang; Zhouyue Zhu; Hongqiang Shen (BMC Infectious Diseases)
Abstract Objective To explore the influence of respiratory infections on the onset of Henoch-Schönlein Purpura (HSP) in children, along with exploring potential underlying mechanisms. Method The present study conducted a statistical analysis on renal involvement indicators in 296 children with HSP who came to the Children’s Hospital of Zhejiang University, as well as the IgA levels in 400 children with respiratory infections and 400 children with HSP. Results Compared with the control group, children with HSP exhibited a significant increase in urine red blood cell count, urine microalbuminuria, and urine protein/creatinine ratio (P < 0.001). The monthly outpatient visits for children with respiratory infections exhibited a similar pattern to those with HSP, demonstrating a heightened prevalence during the autumn and winter. The level of IgA in children with respiratory infections and HSP were significantly higher than those in the control group (P < 0.001). Conclusion HSP can give rise to complications such as renal involvement. There exists a certain correlation between respiratory infections and the occurrence of HSP, which may be attributed to the elevation of IgA induced by respiratory infections. In conclusion, children with HSP should reinforce protective measures during the peak influenza season in order to prevent respiratory infections.